ยุทธศาสตร์เชิงรุกด้านการจัดการความรู้ในโรงพยาบาลมหาวิทยาลัยนเรศวร: Approach Strategies of Knowledge Management in Naresuan University Hospital - Liampreecha, Wasin; Chaiyaput, Weerapong (Asian Health, Science and Technology Reports, 2011)
The purpose of this research was to measure firm performance of using approach strategies and key success factors in knowledge management. Naresuan University Hospital related environment was selected to test the proposed hypotheses and to analyze qualitative data because of the many knowledge work settings and work performances that are available in this context. Data were collected from 38 survey participants and 3 interviewees. The results of the analysis supported the hypothesis that learning strategic management model had positive affected on nature of knowledge and organizational learning, strategic management of organization, knowledge management and the linking of knowledge management with an aggressive strategy of the organization. Nature of knowledge and organizational learning, strategic management of organization, knowledge management and the linking of knowledge management with an aggressive strategy of the organization also had a significant direct impact on firm performance, as well as key success factors to firm performance.